PERBANDINGAN SISTEM SAPAAN KEKERABATAN BAHASA BANJAR DENGAN BAHASA MELAYU SUNGAI GUNTUNG - Abdul Rahman; Hasnah Faizah; Auzar Auzar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study looks at the comparative greeting kinship system with Malay language Banjar Guntung River. This study aimed to describe the system greeting relationship with the Malay language Banjar Guntung River. The method used in this research is descriptive method based on facts and data obtained in the field. Data collection for this research using interview techniques and information from informants and documentation techniques include. The results of the research I have discovered have shown in this study that the relationship greeting Malay language Banjar system and offer guidance to people who are bwlood relations penyapa greet directly or marriage.Keywords: Systems of designation of kinship, Banjar language and Malay